Community awareness regarding smokeless tobacco (Shamma) as a cause of oral cancer in Jazan region, Saudi Arabia: A cross-sectional study - Fatimah H. Dallak; Fahd A. Alharbi; Abdulaziz H. Alhazmi; Faisal Abusageah; Amjad A. Durayb; Norah M. Almalki; Faisal A. Abu Tayrah; Maged El-Setouhy; Rawan H. Dallak; Ruqayyah M. Shami (Journal of Family Medicine and Primary Care)
Introduction: Oral cancer has emerged as a significant public health issue, with 90% of instances because of avoidable causes. Smokeless tobacco usage is thought to be a substantial source of cytological alterations in the oral mucosa, and snuff (Shamma) is often used in Saudi Arabia. In this study, we investigated community awareness of Shamma as a cause of oral cancer in the Jazan region’s general population. Methods: A cross-sectional A self-administered questionnaire was used in analytical research of people in the Jazan region to determine their awareness of Shamma consumption and its association with oral cancer. The collected data were analysed with SPSS software. Results: About 1380 participants were included in the study. 730 (52.9%) were females and most of the participants (63%) were between eighteen and thirty years old. About three-quarters 1022 (74.1%) of the participants had previously heard about oral cancer, 457 (44.7%) stated that it is possible to avoid oral cancer and 593 (58%) mentioned that oral cancer is treatable. About 45.1% of the participants believe that older ages are risk factor of oral cancer. Concerning awareness of the warning oral cancer’s symptoms and signs; more than half (76.9%) mentioned oral ulcers. Regarding knowledge about risk factors for oral cancer; the most often mentioned ones were smokeless tobacco (87%), smoking (86%), followed by khat chewing (62.1%), and alcohol (58.9%). About 66.2% of the participants have tried to stop Shamma in the past 12 months. We found that gender and age are a risk factor for oral cancer, where they are correlated significantly with knowledge and awareness of smokeless tobacco (P value < 0.001 and 0.049, respectively. Conclusion: Good overall awareness and knowledge about Shamma and smokeless tobacco. More than half of the individuals recognized Shamma as an oral cancer risk factor with accuracy. Oral ulcers were revealed to be the most well-known sign of oral cancer among survey participants. It was shown that there was a significant correlation between gender awareness and knowledge levels. In addition interventional research is necessary.